10 % fluorescein sodium vs 1 % isosulfan blue in breast sentinel lymph node biopsy. Issue 1 (December 2016) - Ren, Lidong; Liu, Zhao; Liang, Mengdi; Wang, Li; Song, Xingli; Wang, Shui
Abstract Background Sentinel lymph node biopsy (SLNB) is well accepted to be a standard procedure in breast cancer surgery with clinically negative lymph nodes. Isosulfan blue is the first dye approved by the USA Food and Drug Administration for the localization of the lymphatic system. Few alternative tracers have been investigated. In this study, we aimed to compare the differences between 10 % fluorescein sodium and 1 % isosulfan blue in breast sentinel lymph node biopsy and to investigate the feasibility of using 10 % fluorescein sodium as a new dye for breast sentinel lymph node biopsy. Methods A total of 30 New Zealand rabbits were randomly divided into the fluorescein sodium group and the isosulfan blue group (15 rabbits per group). Fluorescein sodium or isosulfan blue was injected subcutaneously into the second pair of mammary areolas. Results The average fading time of the second lymph nodes in the isosulfan blue group was significantly shorter than that in the fluorescein sodium group. Moreover, the detection rates of SLNs were higher in the fluorescein sodium group than in the isosulfan blue group. No significant differences between the fluorescein sodium group and isosulfan blue group were observed regarding the distances between the detected sentinel lymph nodes and second pair of mammary areolas, the distances between the second lymph nodes and second pair of mammary areolas, the number of detected sentinel lymph nodes and second lymph nodes, the average dyeing time of the sentinel and the second lymph nodes, and the average fading time of the second lymph nodes. Conclusions In summary, we first reported that fluorescein sodium is a potential new tracer for breast sentinel lymph node biopsy.